Preferensi Masyarakat Kota Surakarta terhadap Pemilihan Angkutan Umum - Vania Mirza Eriyanti; Widjonarko Widjonarko (Jurusan Perencanaan Wilayah dan Kota, 2019)
The growth of Surakarta City that occurs continously, causing an increase in the daily activities of its city community. Surakarta city community are urgently need public transportation service both facilities and infrastructure, to support the increasing daily activities. Surakarta City government creates the Surakarta City Government's Mass Public Transport Facility Improvement Program (SAUM) which aims to reduce the number of private vehicle use in Surakarta City and divert the interest of the public to use Batik Solo Trans (BST). BST procurement as the main public transportation facility in Surakarta are the sub program that include in the SAUM. The steps that will be taken by the city government started by planning the construction of six BST corridors and the gradual replacement of existing public transport to BST. The public transportation that will be replaced are city bus and city transportation (angkot). The problem in the planning is the unbalanced needs of the community for convenient, fast, integrated and inexpensive transportation with the existing public transportation facilities. This causes a reduction in public interest in using public transport. It also causes other problems to arise, namely more and more people who choose to use private vehicles to support their daily activities. Based on the plan of the Surakarta City Government and the situation in the field, the formulation of the problem was formulated with a research question